Evaluation Of The Effectiveness Of The Parliamentary Supervision Mechanism On Executive Performance In The Indonesian Constitutional Legal System - Saharuddin Saharuddin; Andi Bau Mallarangeng; Abdul Aziz (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This research aims to evaluate the effectiveness of the monitoring mechanism carried out by parliament on executive performance in the Indonesian constitutional law system. Parliamentary oversight of executive policies is an important mechanism for maintaining accountability and transparency in government. However, concerns remain regarding how much this mechanism effectively meets its objectives. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with members of parliament, executive officials, and constitutional law experts. Additionally, analysis of documents and policies related to parliamentary oversight was also carried out. This research shows that although the parliamentary oversight mechanism for executive performance has been regulated in law, several challenges hinder its effectiveness. These challenges include limited time and resources available to parliament, a lack of understanding of the role and authority of parliamentary oversight, and political factors that influence parliamentary independence. Apart from that, this research also found that good cooperation and communication between parliament and the executive is essential in increasing the effectiveness of supervisory mechanisms. Transparency in information delivery, open dialogue between the two institutions, and a follow-up mechanism for monitoring findings can also strengthen the effectiveness of parliamentary oversight of executive performance. This research enriches understanding of parliamentary oversight mechanisms in the Indonesian constitutional law system. It is hoped that the results of this research can become a basis for improving and strengthening parliamentary oversight mechanisms to be more effective in maintaining accountability and transparency in government.